ANALISIS KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN GO PUBLIK DI PASAR MODAL - Lisa Kartikasari; Luluk M. Ifada (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
The purpose of this research was examining financial reporting timeliness (annual report)that go public at Indonesia Stock Exchange. Indicator of characteristic information at capitalmarket is most actually information which timeliness. Timeliness constitutes main problem sothere is trend for public’s firms to mistiming deep to pass on financial statements to BAPEPAM.The effect this research is subject to be analized discipline or compliance zoom thatgets bearing with financial reporting and to find empiric prove hits factors that regard corporatefinance reporting timeliness that go public at Indonesia Stock Exchange. Samples in thisresearch are 198 firms that go public at Indonesia Stock Exchange in year 2003 untill 2005.This research used binary logistic’s regression by use of program SPSS 13. To determine andchooses best fit model in hypothesis testing was done by estimation by use of two scenario.Result of this research : (1) Size, age and insider ownership impact of corporate finance reportingtimeliness. (2) Debt to equity ratio, profitability and outsider ownership did not impactof corporate finance reporting timeliness.Keywords: Debt to Equity Ratio, Profitability, Outsider Ownership, Insider Ownership